KORELASI ANTARA MINAT BACA DAN MOTIVASI DENGAN NILAI KOGNITIF DALAM PEMBELAJARAN TEMATIKKELAS V - Fitri Sari Utami; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine whether or not there is a correlation between reading interest and motivation with students' cognitive scores in thematic learning in class V of 35 South Pontianak Elementary School. The research method used is descriptive method with the form of relationship studies research using correlation studies. The population in this study amounted to 109 students and the sample used was 33 students. Data collection techniques in this study are indirect communication techniques and documentary study techniques. The instrument (data collection tool) of this research is in the form of a questionnaire (questionnaire) and cognitive value documents. Based on the results of statistical calculations using multiple correlations calculated using SPSS 26 to calculate the correlation between reading interest and learning motivation with students' cognitive values obtained rcount of 0.132, while rtable for N = 33 and 5% significance level of 0.344 means rcount < rtable or 0.132 < 0.344. Based on the results of the study, there is a correlation between interest in reading and learning motivation with students' cognitive scores in thematic learning in class V of 35 South Pontianak Elementary School and is included in the very low category.Keywords: Cognitive Value, Correlation, Interest In Reading, Learning Motivation